PELATIHAN PENGELOLAAN KEUANGAN RUMAH TANGGA BAGI WANITA NELAYAN DI DESA NENAS SIAM KABUPATEN BATU BARA - Azizah Mahary; Irham Huspa Siregar; Asep Gunawan (Universitas Mataram, 2023)
Family financial management is a fundamental skill that must be owned by every household. The wife has an important role in managing family finances because the wife's job is to be the